MENGGALI PERSEPSI WAJIB PAJAK ATAS KEPUASAN PENDAMPINGAN PELAPORAN SURAT PEMBERITAHUAN (SPT) OLEH RELAWAN PAJAK - Sandra Lista Wati; Soesilawati Soema Atmadja (Ekomania, 2023)
This study aims to determine the perception of Taxpayers (WP) on the satisfaction of reporting assistance for Annual Tax Returns (SPT) conducted by Tax Volunteers (RP) KPP Pratama Surabaya Tegalsari. This research method uses a qualitative descriptive approach. The sample selection in this study was conducted using online and offline interview techniques to collect research data. The population in this study is the Individual Taxpayer (WPOP) who reports the Annual SPT assisted by Tax Volunteers in all tax service offices in Surabaya. As for the sample in this study, namely taxpayers who are assisted by KPP Pratama Surabaya Tegalsari Tax Volunteers when filling out the WPOP SPT. This study found that the assistance activities for filling out the SPT WPOP carried out by Tax Volunteers in order to help taxpayers were considered very effective. This can be seen from the results of interviews conducted with both Taxpayers and Tax Volunteers who explained that Taxpayers were greatly helped and felt satisfaction after being accompanied by Tax Volunteers when reporting SPT WPOP. Most of the Taxpayers are satisfied with the existence of this Tax Volunteer program because the process of reporting the Taxpayers' Annual Tax Return becomes easier and not long, the Tax Volunteers are able to guide Taxpayers in filling out their Annual SPT. With this program, it is able to reduce the difficulties felt by taxpayers when filling out their annual tax returns and it is hoped that in the future it can increase taxpayer compliance in reporting their annual tax returns.